A Fe/Mn‐Based Prussian Blue Analogue as a K‐Rich Cathode Material for Potassium‐Ion Batteries. Issue 9 (20th June 2017) - Jiang, Xi; Zhang, Tianran; Yang, Liuqing; Li, Guochun; Lee, Jim Yang
Abstract: The reversible intercalation of K + into graphite has spurred interest in new rechargeable battery chemistries based on potassium ions. The viability of commercializing potassium‐ion batteries (KIBs) is critically dependent on the availability of pre‐potassiated cathode materials, and the compatibility between the electrolyte and electrode components; which have yet to be fully explored. Herein, we report a Fe and Mn based K‐rich Prussian Blue analogue, which can be used as the cathode of rechargeable KIBs to deliver 115 mAh/g of discharge capacity with two voltage plateaus at 3.9 and 4.1 V vs. K + /K in an electrolyte with fluoroethylene carbonate additive. In half‐cell studies, the cyclability of this Prussian Blue analogue was found to depend on the formation of a passivation layer on the anode and the decomposition of the active electrode material at the cathode. This study demonstrates the importance of electrode−electrolyte compatibility in the development of new rechargeable battery chemistries, especially when the evaluation is based on half‐cell studies where potassium metal is used. Abstract : A volt of confidence : A high‐voltage potassium‐rich cathode for potassium‐ion batteries is synthesized and characterized. The study also detects the incompatibility between a commonly used electrolyte [1 M KFSI in 1:1 (v/v) EC: DEC] and the potassium metal, resulting in large overpotentials and cell failures. FEC is an effective additive that reduces many of the cell debilities, but it also shows some reactivity towards KMFC.